Kako zmanjšati število napotitev in izboljšati njihovo kakovost? - Živčec Kalan, Gordana (Medicinski razgledi, 2005)
It has been shown that in Slovenia the percentage of referrals to specialists is relatively high compared to other European countries. At the same time, thereferral quality is low. This paper analyses reasons for referral. Some suggestions are provided on how to reduce the number of referrals and how to improve their quality. The former task turns out to be difficult if one uses only the administrative measures, while the latter is more feasible and is accompanied by an improvement in working efficiency.
Keywords: Družinska medicina; Family Practice; Poklicni odnosi; Referral And Consultation; Posvetovanje in napotila; Interprofessional Relations; ambulantna oskrba; napotitve (medicina); specialistične ambulante; organizacija zdravstva